CLINICO-LABORATORY MARKERS OF PREMENOPAUSAL OSTEOPOROSIS - Zaripova , D.Ya.; Tuksanova , D.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Relevance. With the improvement in the quality of life, a person began to live longer, this situation has led to the fact that women today spend 1/3 of their lives in the perimenopausal period. But this period has its own long-term problems in the form of osteoporosis. The purpose of the study. To determine the biochemical markers of osteoporosis in the early stages of its development. Materials and methods. We selected 121 women of the perimenopausal period as the object of the study, they were divided into 3 groups. Research results. The level of magnesium, calcium and estradiol in women with normopenia was higher than in patients with osteopenia and osteoporosis. In addition, the level of alkaline phosphatase and T-test in densitometry, on the contrary, was increased. Conclusion. The use of MHT in the form of a transdermal spray and metabolic therapy (calcium D3, aleandronic acid), in the osteopenic stage, makes it possible to prevent osteoporosis.